The role of husbands’ social support and women’s knowledge on the selection of long-term contraceptive methods - Venny Vidayanti; Listyana Natalia Retnaningsih (Jurnal Kesehatan Ibu dan Anak, 2020)
The low level of women’s knowledge regarding the benefits and side effects of LTCM as well as the growing negative myths around the application of LTCM will cause a low intention in using LTCM. The husband support in using LTCM holds a crucial role for wives in taking their decision to use LTCM. This study aimed to discover the correlation between husbands’ social support and women’s knowledge on the selection of LTCM in rural areas of Yogyakarta. This study used a cross-sectional design that involved 60 active acceptors of reproductive age women in Karangsari Village, Ngemplak, Sleman. The sampling technique was simple random sampling and bivariate analysis in this study used Chi-Square test. The findings of the study showed 53,3% women decided to choose LTCM and 46,7% women used non LTCM method. The results of chi-square test were 0.466 of p-value between knowledge variable and LTCM selection, and 0.028 of p-value with 3.21 of odds ratio score (95%CI=1.09-9.44) between husband’s social support variable and LTCM selection. This study concluded that the husband’s social support affects wives in choosing the long-term contraceptive methods while the mother’s knowledge is not related to LTCM selection. Mothers who receive positive support from their husbands will have 3.21 times the chance of using LTCM methods.